2017
DOI: 10.3389/fncel.2017.00079
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of PDGF-AA-Overexpressing Oligodendrocyte Precursor Cells Promotes Recovery in Rat Following Spinal Cord Injury

Abstract: Our previous study showed that Schwann cells (SCs) promote survival, proliferation and migration of co-transplanted oligodendrocyte progenitor cells (OPCs) and neurological recovery in rats with spinal cord injury (SCI). A subsequent in vitro study confirmed that SCs modulated OPC proliferation and migration by secreting platelet-derived growth factor (PDGF)-AA and fibroblast growth factor-2 (FGF)-2. We also found that PDGF-AA stimulated OPC proliferation and their differentiation into oligodendrocytes (OLs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
5
17
0
Order By: Relevance
“…animals (Keirstead et al, 2005). Given the cavity size reduction and functional recovery in both OPC and hEnSC groups, consistent with the findings of Yao et al (2017), we can indicate that the obtained functional recovery might be related to cavity size reduction.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…animals (Keirstead et al, 2005). Given the cavity size reduction and functional recovery in both OPC and hEnSC groups, consistent with the findings of Yao et al (2017), we can indicate that the obtained functional recovery might be related to cavity size reduction.…”
Section: Discussionsupporting
confidence: 87%
“…Sharp, Frame, Siegenthaler, Nistor, and Keirstead (2010) and Keirstead et al (2005) We evaluated the morphology of injured spinal cord using H&E staining and found a significant reduction in the cavity size in the injured site of animals that received OPCs and hEnSCs compared to vehicle and SCI groups but no significant difference was found between the OPC and hEnSC groups. In another study by Yao et al (2017), they found increased tissue repair in SCI model after transplantation of PDGF-AA-overexpressing OL precursor cells followed by the reduction in the lesion size and they suggested that reduction in lesion volume was a cause of functional recovery. In contrast, Keirstead et al (2005) have reported the reduction of cavity size in both hFB (human fibroblast) and OPC-transplanted animals but they found the improvement of functional recovery only in the OPC group, which indicates that the reduction in the cavity size is not the reason for functional recovery in OPC-transplanted F I G U R E 5 (A) Luxal fast blue staining was used to evaluate the rate of myelination in different groups under the study 10 weeks after cell transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…In vitro oligodendrocyte cultures can be useful for both cell therapy and drug screening purposes. Currently, in vitro expansion of oligodendrocyte lineage cells can be obtained by (i) sorting of oligodendrocyte precursors from postnatal or adult brain tissue ( Zhu et al, 2007 ; Pedraza et al, 2008 , 2014 ; Fumagalli et al, 2011 , 2015 ; Dugas and Emery, 2013a , b ; Emery and Dugas, 2013 ; Medina-Rodríguez et al, 2013 ; Lu et al, 2015 ); (ii) culturing and differentiating ESCs into oligodendrocytes ( Glaser et al, 2004 ; Zhang et al, 2004 ; Chojnacki and Weiss, 2008 ; Jiang et al, 2010 ; Neri et al, 2010 ; Sundberg et al, 2010 ; Sharp et al, 2011 ; Neman and de Vellis, 2012 ; Alsanie et al, 2013 ; Franco et al, 2015 ; Kerman et al, 2015 ; Wang et al, 2015 ; Yamashita et al, 2017 ; Yao et al, 2017 ) and (iii) generating and differentiating oligodendrocytes from patient-derived iPSCs ( Khazaei et al, 2007 ; Hu et al, 2009 ; Czepiel et al, 2011 ; Ogawa et al, 2011 ; Sundberg et al, 2011 ; Douvaras and Fossati, 2015 ; Gorris et al, 2015 ; Li et al, 2016 ; Kim et al, 2017 ; Rodrigues et al, 2017 ). All these available methods present some pitfalls that limit their clinical exploitation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that PDGF-A positively modulates OL lineage cells via synergistic effects with components of the extracellular matrix and other pro-proliferation growth factors, such as FGF-2 and IGF-1, which are upregulated for weeks after SCI [68,164,[189][190][191]. After experimental rat SCI, intraspinal transplantation of Schwann cells promotes host OPC proliferation and recruitment to the lesion via secretion of FGF-2 and PDGF-A, a treatment that promoted remyelination of spared axons and enhanced recovery of function [188]. Further studies evaluating the synergistic effects of these protective, pro-OL lineage growth factors could provide novel therapeutic avenues that robustly promote OPC proliferation and differentiation.…”
Section: Growth Factorsmentioning
confidence: 99%
“…OPC differentiation and remyelination of spared axons are also modulated post-injury by PDGF-A, which primarily upregulates Olig2 [61,188]. Evidence suggests that PDGF-A positively modulates OL lineage cells via synergistic effects with components of the extracellular matrix and other pro-proliferation growth factors, such as FGF-2 and IGF-1, which are upregulated for weeks after SCI [68,164,[189][190][191].…”
Section: Growth Factorsmentioning
confidence: 99%